(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY Fetal abnormalities found on ultrasonography lead to a variety of diagnostic procedures, including a panel of serologies to detect possible maternal STORCH infections encompassing syphilis, Toxoplasma gondii, rubella, cytomegalovirus, herpes simplex, and others (human immunodeficiency virus, hepatitis B and C, parvovirus B19, enterovirus, varicella zoster, and Leptospira interrogans). The value of indiscriminate testing for infections upon the detection of fetal ultrasound abnormalities has been questioned. The aim of this study was to review the ultrasonographic abnormalities leading to maternal STORCH panels at the obstetrics department of a university hospital. METHODS Laboratory results of all maternal STORCH tests requested after the detection of ultrasonographic abnormalities during a 5-year period (2008–2012) were analysed. The main ultrasound findings possibly caused by congenital infection were noted, and the outcomes of confirmed maternal and fetal infections were studied. RESULTS In our study period, 392 maternal STORCH tests were performed because of fetal ultrasound abnormalities. The most common findings leading to STORCH testing were intrauterine growth restriction (30.4%) including microcephaly (1.5%), polyhydramnios (14.8%), and intrauterine fetal demise (13.3%). Maternal STORCH infections were found in 3.4% of growth-restricted fetuses, 5.2% of polyhydramnios, and 1.9% of intrauterine fetal demise. The leading aetiologies were cytomegalovirus and parvovirus B19. All seven congenital infections displayed multiple ultrasonographic abnormalities. CONCLUSION Ultrasonographic findings associated with fetal infection are neither sensitive nor specific. Testing for STORCH infections should take into account exposure history, clinical signs and symptoms, obstetric history, and fetal ultrasound findings, but with special attention paid to cytomegalovirus and parvovirus B19.